Pelaksanaan Kegiatan Ekstrakurikuler Tenis Meja di SMA Negeri 1 Bengkulu Selatan - Wibowo, Tito Parta; Juniardi, Arifto; Perdima, Feby Elra (UNIVED Press, Universitas Dehasen Bengkulu, 2020)
The problem in this study is the lack of extracurricular implementation of table tennis because several factors affect it, including facilities and infrastructure, student motivation, and parental support. This study aims to reveal the description of the implementation of table tennis extracurricular activities in SMA Negeri 1 Bengkulu Selatan. This type of research is descriptive. The population in this study was 30 people consisting of SMA Negeri 1 Bengkulu South students who were active in participating in table tennis extracurricular consisting of 21 sons and 9 daughters. Sampling is done by the Saturated Census (Saturated Census) technique, which is by taking the whole population, so the sample is 30 people. The results obtained from the implementation of Table Tennis Extracurricular Activities in SMA Negeri 1 Bengkulu Selatan are facilities and infrastructure in the Good category, student motivation is classified Good, and parental support is in the Good classification